Diagenetic Controls on Porosity in Sandstones of the Talang Akar Formation: A Case Study from the Rambangnia River Track, South OKU, South Sumatra - Rochmana, Yogie Zulkurnia; Jati, Stevanus Nalendra; Puspita, Mega; Idarwati, Idarwati; Pranata, Ridho (Jurnal IPTEK, 2025)
Porosity contributes to fluid storage and determines reservoir quality. The higher the porosity, the more free space is available to store fluid. However, the porosity of reservoirs, particularly the sandstones of the Talang Akar Formation of the Rambangnia River track, is not always good. The diagenetic process in the formation of sandstones is thought to contribute to variations in porosity quality. This study aims to determine the control of diagenesis on the porosity of sandstones of the Talang Akar Formation of the Rambangnia River, South Sumatra. The research methods used were field observation, petrographic, diagenesis, and porosity analysis. Based on petrographic analysis, the study area has three types of sandstone: lithic wacke, sublitharenite, and litharenite. The study of diagenesis shows that the sandstones in the Rambangnia River’s Talang Akar Formation have gone through an intense compaction phase, dissolution, cementation by silica and calcite minerals, and an authigenic phase in clay minerals.  In general, the porosity of rocks in the study area ranges from fair to good.